Business Strategy Development in Improving Organizational Performance Using SWOT Analysis, IE Matrix and QSPM - Praja, Fikry Andias; Triono, Sunu Puguh Hayu (Journal Research of Social Science, Economics, and Management, 2026)
Education plays a strategic role in the social and economic development of a nation. However, educational institutions in Indonesia face complex challenges, including graduate competency mismatch, declining service quality, and limitations in resources and technology. Yayasan As-Syifa Al-Khoeriyyah, as an integrated Islamic educational institution, has also experienced a decline in organizational performance, as indicated by a decreasing number of students over recent years. In addition, dependence on a single funding source and limited innovation in human resources have become major issues. This study aims to identify internal and external factors affecting organizational performance and to formulate appropriate business strategies to improve managerial effectiveness and institutional sustainability. The research employs a strategic management approach based on Fred R. David's model, which includes the input stage using the External Factor Evaluation (EFE) and Internal Factor Evaluation (IFE) matrices, the strategy-matching stage through SWOT and IE matrices, and the decision stage using the Quantitative Strategic Planning Matrix (QSPM). The results indicate an IFE score of 2.85 and an EFE score of 3.02, placing the organization in a development-oriented position that requires a focus on market development, product development, and integration across all organizational functions. The IE matrix shows that Yayasan As-Syifa Al-Khoeriyyah is positioned in Regions I and II, reflecting a "Grow and Build" strategy. Furthermore, the QSPM analysis identifies the priority strategy as developing nationally competitive flagship programs based on an integrated curriculum encompassing academic excellence, character, and moral education, along with enhancing teacher competencies.